PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL TRHOWING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SDN 79 BALAI MAKAM KECAMATAN MANDAU KABUPATEN BENGKALIS - Maizuarni Maizuarni; Lazim N Lazim N; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak : This research was conducted because of the result of learning IPS class V SD Negeri 79 Balai Makam. From 24 student who achieve KKM just 10 student (41,6%) while student who did’nt complete 14 student (58,33 %) with an average of 56,88. This aims of study to increase the study result IPS school years 2015-2016. This research subjet are student class V SDN 79 Balai Makam Kecamatan Mandau kabupaten Bengkalis. This research is the action research is class action with two cycle. Teacher activity cycle one on the first appointment teacher activity presentation are 62,5% with the enough category increase to 75% with the good category on the second appointment and the one cycle two appointment back to 83,3% with the excellent category and two cycle two appointment back to increase to 91,7% with the excellent category. The students activity from each appointment incease effect. Cycle two on the first appointment students activity presentation are 58,3% with the enough category increase to the second appointment to 66,7% with the enough category and the one cycle two appointment increase again to 79,2% and the two cycle two appointment increase to 87,5% with the excellent category. The stdents result can increase after used cooperative type Snowball Throwing are 10 students can complete with the basic score with amount of 1365 (56,88) increase to daily exam 1 amount of 37,7% to 24 students with the score 1880 (78,33). And than fro daily exam II increase a lot of 65,5% to 24 students with the score 2260 (94,71). Therefore can concluded that hypothesis in creases can applied the teamry model cooperative type Snowball Throing can increase the studies result IPS students class V SDN 79 Balai Makam kecamatan Mandau Kabupaten Bengkalis.Keywords : Snowball Throwing, Learning Outcomes IPS